BS13 Role for microRNA-26B in vessel calcification. (May 2019) - Mellis, David; Martello, Andrea; MacAskill, Mark; Elemans, Loes; Angel, Souzana; Al-Haj Zen, Ayman; Tavares, Adriana; Forsythe, Rachael; Jones, Ross; Wagner, Brad; Newby, David; Baker, Andrew; et al.
Abstract : Introduction: MicroRNAs (miRNAs) are small non-coding RNAs that orchestrate genetic networks by modulating simultaneous gene expression and regulates vascular function. Despite recent accumulation of experimental data and the emergence of functional models, the complexity of miRNA-based regulation is still far from being well understood. By performing high-content phenotypic screening (HCS), miR-26b emerged from the screen as a top candidate for ECs proliferation. The overexpression of miR-26b significantly increased EC proliferation, migration and survival. Furthermore, miR-26b mimics increased EC tube formation and branching morphogenesis. HCS and bioinformatic analysis identified both Phosphatase and Tensin homolog (PTEN), a gene critical in cell survival and Bone Morphogenetic Protein Receptor Type 1B (BMPR1B; ALK6), important in calcium homoeostasis, as direct targets of miR-26b. Because BMPR1B was identified as a direct target of mir-26b, we decided to study the role of miR-26b in vessel calcification. To test our hypothesis, miR-26b CRISPR/Cas9 global knock-out (KO) mice were generated. Objective: The aim of this study is to characterize how miR-26b can influence vascular calcification and characterize ALK6 as mir-26b target. Methods: In this study, we have used HCS and miR-26b KO mice and artery from patients with critical limb ischaemia to prove our hypothesis Results: We confirmed that miR-26b was knocked down in the miR-26b KO mice without effecting the expression of other miR-26 family members and the host gene. To test whether miR-26b KO mice were more susceptible to calcification, we extracted the heart and aorta from 3-month-old mice and cultured for 6 days in a high phosphate media with and without warfarin. Histological analysis with the calcium stains von Kossa and alizarin red confirmed that miR-26b KO mice displayed a higher level and susceptibility to calcifying compared to control mice. Expression of the markers of calcification (RUNX2 & ALK6) supported the histology. Immunohistochemistry and qPCR confirmed that the expression of ALK6 was also increased in the miR-26b KO. To further characterise this phenotype, mice were aged and multiple tissues including the aorta were harvested from 3 and 6 month old mice. The aorta and hearts were then prepared for high resolution PET/CT using the highly calcium specific sodium fluoride (18F) probe. This probe allows for the detection of both micro and macro calcification. PET/CT supported our ex-vivo culture model and confirmed that 6-month-old miR-26b KO mice had a higher level of micro-calcification compared to control mice. To investigate the clinical relevance of miR-26b, we analysed artery and muscles from below the knee amputated limbs from patients with critical limb ischaemia. The levels of miR-26b was decreased in the muscle biopsy from the less perfused section of the amputated leg compared to more perfused counterpart. Moreover, miR-26b was downregulated in the calcified tissue portion of the artery in comparison to the soft tissue. Conclusion: Taken together these findings demonstrate an important role for miR-26b in vessel calcification and suggest its effects are through the upregulation of BMPR1B; Alk6. Conflict of interest: None